Concepts and Dimensions of Human Dignity in the Christian Tradition - Müller, Sigrid (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
This paper investigates the extent to which Christian tradition can be used to support human dignity and human rights in contemporary society. It explores the Christian tradition for ideas that correspond to the four main dimensions of human dignity: anthropological, moral, legal, and practical. It examines how these dimensions relate to the two main Christian perspectives that define human dignity, namely the imago Dei paradigm and dignity of the human soul or person. Concluding observations demonstrate that the corresponding Christian ideas offer a solid foundation for developing a strong Christian narrative and engagement in support of human dignity and human rights. However, an analysis of the two dominating concepts also indicates that a reception that excludes the universal aspect of the imago Dei paradigm can endanger a full acceptance of human dignity and human rights. Therefore, it is necessary to continue existing ecumenical efforts to create a complementary reading of the two traditions.